2020
DOI: 10.1021/acsenergylett.0c00514
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Tolerant Sodium-Based Dopant in Charge Transport Layers for Highly Efficient and Stable Perovskite Solar Cells

Abstract: To extract charges more efficiently through charge-transporting layers (CTLs), various dopants are necessary. Lithium bis­(trifluoromethanesulfonyl)­imide (Li-TFSI) is the most widely used dopant in electron- and hole-transporting layers. However, Li+ ions easily migrate into the perovskite and deteriorate the device performance. To address this issue, several efforts such as introducing a buffer layer have been tried, but the issue is still not fully resolved. Thus it is required to find a simple way without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…22.4 >500 h FTO/TiO 2 (Na-TFSI)/(FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 / spiro-OMeTAD(Na-TFSI)/Au AM 1.5 G, 45 °C TiO 2 (Na-TFSI) [234] (suppressed ions migration by Na-TFSI) 2020 18.2 >500 h FTO/TiO 2 (0.1CL-GP)/Perovskite/spiro-OMeTAD/Au AM 1.5 G, N 2 TiO 2 (0.1CL-GP) [235] Besides spiro-OMeTAD, many small organic HTMs also suffer from similar problems, as the dopants therein usually induce pinholes in the layer or react with perovskite. [251] There are three ways to address these problems: 1) inserting a compact blocking layer between the HTL and perovskite layer, 2) finding a new HTM that is friendly to perovskite layer and compact enough to block the migrating ions, 3) developing new HTMs without dopants.…”
Section: Photoinduced Effect On Small Organic Htlsmentioning
confidence: 99%
“…22.4 >500 h FTO/TiO 2 (Na-TFSI)/(FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 / spiro-OMeTAD(Na-TFSI)/Au AM 1.5 G, 45 °C TiO 2 (Na-TFSI) [234] (suppressed ions migration by Na-TFSI) 2020 18.2 >500 h FTO/TiO 2 (0.1CL-GP)/Perovskite/spiro-OMeTAD/Au AM 1.5 G, N 2 TiO 2 (0.1CL-GP) [235] Besides spiro-OMeTAD, many small organic HTMs also suffer from similar problems, as the dopants therein usually induce pinholes in the layer or react with perovskite. [251] There are three ways to address these problems: 1) inserting a compact blocking layer between the HTL and perovskite layer, 2) finding a new HTM that is friendly to perovskite layer and compact enough to block the migrating ions, 3) developing new HTMs without dopants.…”
Section: Photoinduced Effect On Small Organic Htlsmentioning
confidence: 99%
“…For example, sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) was used to dope not only Spiro‐MeOTAD but also TiO 2 ( Figure a). [ 19 ] A high PCE of 22.4% was achieved by simultaneous doping of NaTFSI in ETL and HTL (Figure 8b). ToF‐SIMS showed that Li + ion in Spiro‐MeOTAD was easy to migrate to mesoporous TiO 2 layer through interstitial sites of the perovskite lattice.…”
Section: Nonhalide Dopantsmentioning
confidence: 99%
“…Reproduced with permission. [ 19 ] Copyright 2020, American Chemical Society. d) J‐V curves of the devices using LiTFSI and Zn(TFSI) 2 as dopant for Spiro‐MeOTAD.…”
Section: Nonhalide Dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inorganic HTMs are used in the PSCs due to their excellent properties such as high hole mobility and low cost. Famous examples of HTMs are CuI, 181 CuO x, 182 CuSCN, 183 triarylamine polymer derivatives, 184 PEDOT:PSS, 185 NiO x, 186 polytriarylamine (PTAA), 187 thiophenes, 188 tetrathiafulvalene, 189 poly‐3‐hexylthiophene (P3HT), 190 spiro‐OMeTAD, 191 organometallic compounds, 192 and so on. During the operation hole transporting layer (HTL) has to facilitate the energy conversion process in different form such as high carrier mobility, long carrier lifetime, compatible valence band level between HTL and perovskite, low material and processing cost, and stability during processing.…”
Section: St‐pscs Stabilitymentioning
confidence: 99%